Resistin concentrations in perivascular adipose tissue as a highly sensitive marker of smoking status in patients with advanced coronary artery disease requiring coronary artery bypass grafting - Rachwalik, Maciej; Sareło, Przemysław; Obremska, Marta; Matusiewicz, Małgorzata; Sett, Kaung Sithu; Czapla, Michał; Jasiński, Marek; Hurkacz, Magdalena (Frontiers in Public Health, 2024)
BackgroundSmoking is a significant risk factor for numerous diseases, including coronary artery disease (CAD). Chronic inflammation from smoking affects endothelial function and may alter adipokine secretion, particularly resistin, in perivascular adipose tissue (PVAT). This study investigated the association between resistin concentrations in PVAT and smoking status in CAD patients undergoing coronary artery bypass grafting (CABG).MethodsThe study included 110 patients with advanced CAD scheduled for CABG. Patients were categorized into never-smokers and ever-smokers, with the latter further divided into current and past smokers. Resistin concentrations in PVAT and plasma, along with plasma interleukin-6 (IL-6) and high-sensitivity C-reactive protein (hs-CRP) concentrations, were measured using ELISA.ResultSignificant differences in PVAT resistin concentrations were observed between never-smokers and ever-smokers (p < 0.0001), as well as between never-smokers and both current (p < 0.0001) and past smokers (p < 0.0001). PVAT resistin concentrations correlated positively with the number of pack-years (p < 0.0001) and plasma resistin (p < 0.0001) and IL-6 concentrations (p < 0.0001). Plasma resistin, IL-6, and hs-CRP concentrations were higher in ever-smokers compared with never-smokers. Multiple regression analysis indicated that smoking is significantly correlated with higher PVAT resistin concentrations, with increased pack-years (p = 0.0002), higher plasma resistin concentrations (p < 0.0001), and IL-6 concentrations (p < 0.0001), all contributing to elevated PVAT resistin.ConclusionSmoking status in advanced CAD patients requiring CABG is positively associated with PVAT resistin concentrations, with a clear demonstration of dose-dependency.